Fabrication of Porous Titanium-Hydroxyapatite Composite via Powder Metallurgy with Space Holder Method - Zakaria, M.Y.; Sulong, A.B.; Ramli, M.I.; Ukwueze, B.; Harun, W.S.W.; Mahmud, R.L. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The porous structure of metals has been attracting a growing interest, particularly the use of titanium for bone implants as it promotes cell growth and matches the elastic modulus of the human bone. A porous titanium-hydroxyapatite (Ti-HA) composite was successfully fabricated through the powder metallurgy route using the space holder method. Ti, HA and NaCl space holder were mixed with a binder system consisting of palm stearin (PS) and low-density polyethylene (LDPE). The mixture was later put through a hot press process at a pressure of 20 bars and a temperature of 150 °C. The binders were removed in a two-step process; solvent and thermal de-binding, followed by sintering in a high vacuum furnace at 1300 °C for 5 hours holding time. The Ti-HA at the ratio of 9:1 possessed the best compressive strength and the strength was in the range of 2-70 MPa, which is the range for the trabecular bone of humans. The XRD analysis revealed the existence of a new β-TCP phase due to the decomposition of the HA at a high temperature which resulted in biocompatibility, thereby, indicating a promising prospect for the use of the material in medical implants in the future.